An Electricity Cross-Chain Platform Based on Sidechain Relay. (September 2020) - Wang, Hongkai; He, Dong; Wang, Xiaoyi; Xu, Caichao; Qiu, Weiwei; Yao, Yiyang; Wang, Qiang
Abstract: Based on sidechain relay strategy, a cross-chain platform BitXhub-PI is implemented to realize the interoperability between the heterogeneous blockchains for electric power industry. The platform is composed of three roles: relay chain, application chain and cross-chain pier, and it has three core functional characteristics of universal cross-chain transmission protocol, heterogeneous transaction verification engine, and multi-level routing to ensure the security, flexibility and reliability of cross-chain transactions of electricity business. The platform provides a unified cross-chain contract template for homogeneous and heterogeneous electricity application chains, and the relay chain contains a dynamically upgradeable verification engine. The experiments show that the platform guarantees asynchronous distributed electricity business transactions between heterogeneous blockchains, achieving high performance with high throughput, low latency, high scalability, and low overhead.